Panning peptide libraries on filamentous phage - Travers, Jennifer A., author; Williams, Robert M., advisor (Colorado State University. Libraries, 1996)
This Ph.D. project involved using the filamentous phage as a tool to express peptide libraries on its external appendage called the pIII protein. The peptide libraries were designed based on a motif of the honeybee toxin Apamin. Apamin is expressed on the end of the pIII protein and a portion of the apamin section is randomized to produce all possible combinations of amino acids to give a peptide library. The library phage are then panned on a derivatized solid support to determine if any library members have an affinity to a target ligand. The target chosen is a portion of the peptidoglycan layer in bacterial cells called L-lysine-D-alanine-D-alanine. This is the site for binding of the antibiotic vancomycin. Library members that bind to this site should have vancomycin-like activity. This project entailed preparing the libraries, synthesizing the ligand, and derivatizing a variety of solid supports for panning. Many different panning experiments were performed on several libraries and the results are described herein.
Print version has date: 1997 Summer.
Keywords: Peptides -- Synthesis; Bacteriophages